1990
DOI: 10.1111/j.1099-0860.1990.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Only children in Britain: popular stereotype and research evidence

Abstract: SUMMARY. Only children are popularly believed to be spoiled, lonely and maladjusted, and few parents in Britain choose to have one child. This article documents existing prejudice against only children and their parents, and contrasts it with the very positive picture given by research. Analysis of data from a large scale survey of 16–17 year olds gives a presentation of the family background of only children in Scotland, and confirms that only children do well. The conflict between popular stereotype and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
2
8
0
5
Order By: Relevance
“…When the group of athletes was analysed separately, the results showed significant differences in trait anger, temperament, external anger expression and anger expression index in athletes from non-numerous families. These results follow the previous findings in other fields different than sport, where it was found that single children have worse levels of socialization and greater levels of aggression (Ann, 1990;Doh, 1999;Sui et al, 2015;Tucker & Finkelhor, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When the group of athletes was analysed separately, the results showed significant differences in trait anger, temperament, external anger expression and anger expression index in athletes from non-numerous families. These results follow the previous findings in other fields different than sport, where it was found that single children have worse levels of socialization and greater levels of aggression (Ann, 1990;Doh, 1999;Sui et al, 2015;Tucker & Finkelhor, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Cuando se analizó por separado al grupo de deportistas, los resultados mostraron diferencias significativas en ira rasgo, temperamento, expresión externa de ira e índice de expresión de ira, en los deportistas de familias no numerosas. Estos resultados siguen los hallazgos de los estudios precedentes en otros campos de la vida distintos al deporte, en los que se encuentra que los hijos únicos presentan peores niveles de socialización y mayores de agresión (Ann, 1990;Doh, 1999;Sui, Wang, Liu y Wang, 2015;Tucker y Finkelhor, 2015). Aunque en este trabajo científico dentro del grupo de familias no numerosas se incluyó a las familias con hijos únicos y familias con dos hijos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Such negative stereotyping is prevalent across cultures and is found not only in the United States but also in Great Britain (Laybourn, 1990), Korea (Doh & Falbo, 1999), the Netherlands (Veenhoven & Verkuyten, 1989), and China (Falbo & Poston, 1993), where many critics of China's onechild policy "complained that this policy would ruin the character of the Chinese people" (p. 19). However, numerous studies in the United States, Europe, and Asia have demonstrated that such concerns are simply not true and that, for the most part, only children are not distinguishable from their peers who have siblings.…”
Section: Adriean Mancillasmentioning
confidence: 99%